Characteristics of Positive Deviants in Western Chimpanzee Populations - Heinicke, Stefanie; Mundry, Roger; Boesch, Christophe; Amarasekaran, Bala; Barrie, Abdulai; Brncic, Terry; Brugière, David; Campbell, Geneviève; Carvalho, Joana; Danquah, Emmanuel; Dowd, Dervla; Eshuis, Henk; et al. (Frontiers in Ecology and Evolution, 2019)
With continued expansion of anthropogenically modified landscapes, the proximity between humans and wildlife is continuing to increase, frequently resulting in species decline. Occasionally however, species are able to persist and there is an increased interest in understanding such positive outliers and underlying mechanisms. Eventually, such insights can inform the design of effective conservation interventions by mimicking aspects of the social-ecological conditions found in areas of species persistence. Recently, frameworks have been developed to study the heterogeneity of species persistence across populations with a focus on positive outliers. Applications are still rare, and to our knowledge this is one of the first studies using this approach for terrestrial species conservation. We applied the positive deviance concept to the western chimpanzee, which occurs in a variety of social-ecological landscapes. It is now categorized as Critically Endangered due to hunting and habitat loss and resulting excessive decline of most of its populations. Here we are interested in understanding why some of the populations did not decline. We compiled a dataset of 17,109 chimpanzee survey transects (10,929 km) across nine countries and linked them to a range of social and ecological variables. We found that chimpanzees seemed to persist within three social-ecological configurations: first, rainforest habitats with a low degree of human impact, second, steep areas, and third, areas with high prevalence of hunting taboos and low degree of human impact. The largest chimpanzee populations are nowadays found under the third social-ecological configuration, even though most of these areas are not officially protected. Most commonly chimpanzee conservation has been based on exclusion of threats by creation of protected areas and law enforcement. Our findings suggest, however, that this approach should be complemented by an additional focus on threat reduction, i.e., interventions that directly target individual human behavior that is most threatening to chimpanzees, which is hunting. Although changing human behavior is difficult, stakeholder co-designed behavioral change approaches developed in the social sciences have been used successfully to promote pro-environmental behavior. With only a fraction of chimpanzees and primates living inside protected areas, such new approaches might be a way forward to improve primate conservation.